FUZZY MODELING APPROACH AND GLOBAL OPTIMIZATION FOR DUAL RESPONSE SURFACE - Dedy Dwi Prastyo; Muhammad Sjahid Akbar; Bambang Widjanorko Otok (Institute of Research and Community Outreach - Petra Christian University, 2007)
Dual Response Surface (DRS) with Lagrange multiplier is one of the most familiar classical multi response surface methods. Classical DRS optimization doesn't concern about the quality characteristic of responses. In this paper, fuzzy approach is proposed for modeling DRS and quality characteristic of response simultaneously. The proposed method represented the object's quality characteristic physically. The proposed method is applied to composite carbon drilling process and resulting nonlinear function that to be determined its optimal point. Many optimization methods fail to reach global optimum point because the non linear function is multimodal. Therefore, we used genetic algorithm for finding the global optimum point.